Co-infections of malaria and dengue in Timika, a highly endemic malaria area in Central Papua, Indonesia - Bunga Rana; Leily Trianty; Marsha S. Santoso; Agatha M. Puspitasari; Fahira A. Nisa; Ristya Amalia; Lise Carlier; Kevin Tetteh; Rintis Noviyanti; R. Tedjo Sasmono (PLoS ONE, 2026)
Objective Malaria and dengue are two important infectious diseases in Indonesia, but information about their co-infections is still limited. This study aimed to describe malaria–dengue co-infections in Timika, Papua, including the clinical manifestations and genetic characteristics of the infecting dengue virus (DENV). Methods Sixty-nine microscopy-confirmed malaria patient samples from Timika, a malaria-highly endemic region in Central Papua province, Indonesia collected in 2022 were screened for DENV infection using qRT-PCR. Malaria speciation was performed using qRT-PCR. The whole genomes of the viruses were sequenced using MinION Oxford Nanopore Technology, and the phylogenetic analysis was inferred to determine the origin, genotype, and genetic characteristics of the viruses. Results Out of 69 malaria-positive samples, three patients (4.3%) were co-infected by DENV-2 (1 patient) and DENV-4 (2 patients). The infecting parasites were P. vivax, P. falciparum , and P. malariae as determined using qRT-PCR. The whole genomes of the infecting DENV-4 were successfully sequenced and phylogenetic analysis revealed the genotype of the virus as Genotype II, which were closely related to DENV strains from Makassar city in South Sulawesi province, Indonesia. Conclusions This study demonstrates the occurrence of malaria and dengue co-infections in Timika, Central Papua, Indonesia, with a prevalence of 4.3%. The co-infection poses a unique clinical and diagnostics challenges due to overlapping symptoms and potential complications. This finding highlights the diagnostic difficulties, clinical presentations, and future possibilities for such cases. The genomic data of DENV obtained from these cases provide new information about virus circulation in Indonesia and support the importance of combining clinical and molecular approaches for surveillance.